Early arthritis in children and adolescents — immune status of patients and perspectives of treatment - V A Keltsev; L I Grebenkina; L V Limareva; M A Bochkareva; Y E Grigorjeva (Научно-практическая ревматология)
Objective. To study state of immune status in children and adolescents with juvenile idiopathic arthritis (JIA) at early stages of the disease development and perspectives of their treatment. Materials and methods. 286 children and adolescents with olygo- and polyarticular variants of JIA aged 3 to 18 years were included. Examination of CD4, CD8, CD16, CD95 lymphocyte markers, IgA, IgG, IgM rheumatoid factor, interleukin 1(3, 4, 6, 8, 10, tumor necrosis factor a as well as lymphocyte morphometry was performed. Results. High blood levels of CD4, CD8, CD 16, CD95, pro- and anti- inflammatory interleukins were revealed at active stage of JIA particularly in pts with polyarthritis and extended olygoarthritis. Changes of mean lymphocyte morphometric measures linearly inversely correlated with relative lymphocyte markers level what proves relationship of processes of proliferation, cytotoxicity and elevation of circulating apoptotic cell count in blood. However increase of “programmed death cells" may reflect not only proliferation but also capability of cells to induce cell death program in presence of provocative factors. In pts with very high humoral level of lymphocyte markers and cytokines appropriate therapy more often induces clinico-laboratory remission than in pts with lower values. Conclusion. Immune and cytokine status in children and adolescents with JIA determines evolution of arthritis. Early administration of disease modifying drugs more often induces of clinico-laboratory remission in pts with high levels of lymphocyte markers and antiinflammatory cytokines.